PENGALAMAN AKSEPTOR DALAM MENGGUNAKAN KONTRASEPSI IMPLAN:STUDI KUALITATIF FENOMENOLOGI (LITERATURE REVIEW) - Geby Zahara As-Syifa. Sy; Asmanidar Asmanidar; Yushida Yushida; Juliastuti Juliastuti (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2026)
Background: Implant contraception is one of the Long-Acting Reversible Contraceptives (LARCs) with high effectiveness in preventing pregnancy. Despite its numerous advantages, the use of implants has not been optimal due to various factors, one of which is the subjective experiences of acceptors during use. An in-depth understanding of acceptors' experiences is crucial for improving family planning services and implant coverage in Indonesia. Objective: This study aims to identify and analyze the experiences of acceptors in using implant contraception through a review of various published qualitative phenomenological studies. Method: This study employed a literature review design with a qualitative phenomenological approach. Articles were searched through PubMed, Google Scholar, Garuda, and National Journal Portal databases using keywords such as "pengalaman akseptor implan", "kontrasepsi implan kualitatif", "implant contraception experience", and "phenomenology family planning". Inclusion criteria included journal articles published between 2020-2025, written in Indonesian or English, and discussing acceptors' implant experiences. A total of 23 articles met the inclusion criteria. Results: From the literature review, five main themes of implant acceptors' experiences were identified: (1) reasons for choosing implants, (2) experiences during the insertion process, (3) perceived side effects, (4) psychological and social responses, and (5) satisfaction and continuation of use. The most frequently reported side effects included menstrual cycle changes, weight gain, and headaches. Husband support and healthcare workers were key factors in implant use continuation. Conclusion: Acceptors' experiences in using implant contraception are influenced by physical side effects, social support, counseling quality, and access to healthcare services. Improving the quality of pre-insertion counseling and comprehensive management of side effects is urgently needed to increase implant use continuation.